ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN GAS AMONIA (NH3) PADA PEMULUNG DI TPA JATIBARANG, SEMARANG - Wahyu Sekar Harjanti; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
TPA Jatibarang, Semarang with landfills system of garbage disposal, so garbage that piled up to experience the decomposition in anaerobic and produce a variety of harmful gases i.e. amomonia gas. The unavailability of gas processing installation of ammonia gas causes pollutes the air at TPA Jatibarang and inhaled by the scavenger. The purpose of this research is to analyze the environmental health risk assessment exposure of ammonia gas to scavenger at TPA Jatibarang, Semarang. This research is observational research with cross sectional method. The approach is being used, namely Environmental Health Risk Analysis (EHRA) with a population of subjects are scavengers in TPA Jatibarang as many as 245 people and the population of objects are ambient air at TPA Jatibarang. The sample of this research subjects are 72 people and samples of objects had taken at three point measurements. The results showed that scavengers who live in TPA Jatibarang more risky exposure affected gas ammonia compared with scavenger who resides outside the TPA Jatibarang. The level of risk on a scavenger who resides in TPA Jatibarang for real time projection, is said to be insecure on a scavenger as many as 12 people, while the projection for life time, is said to be insecure on a scavenger as many as 34 people. On a scavenger who resides outside the TPA Jatibarang good projection in real time as well as life time, is said to be still safe on a scavenger as many as 22 people